Smallholders participation in sustainable certification: The mediating impact of deliberative communication and responsible leadership - Rizal, Ammar Redza Ahmad; Nordin, Shahrina Md (Frontiers in Psychology, 2022)
The initiative to ensure oil-palm smallholders around the world participate in sustainable certification is increasing. Different efforts were strategised including increasing awareness and providing financial support. Despite that, the number of smallholders’ participation in sustainable certification is relatively low. This study embarked on the objective to identify the role of social structure, namely social interaction ties in affecting smallholders’ participative behaviours. Moreover, this study is also looking on the mediating impact of deliberative communication and responsible leadership in explaining the relationship between the two previously stated constructs. Using a quantitative research design, this study collected data from 440 smallholders as its respondents. Samples were randomly selected, and questionnaires were distributed to obtain their responses. Data collected were then analysed using PLS-SEM to test the developed hypothesis. Accordingly, the findings indicate that social interaction ties have a significant impact on smallholders’ decisions to participate in sustainable certification. Furthermore, both deliberative communication and responsible leadership were proven to be significant mediators. This study provides insights on how smallholders’ participation in sustainable certification can be improved by tapping on the social structure elements as well as adopting deliberative communication and responsible leadership as a method to communicate and lead with the smallholders. This shall expand literature related to organisation psychology in rural areas and sustainability.